Incidence of Gall Bladder Perforation During Laparoscopic Cholecystectomy in Mosul, Iraq - Salih, Ahmed A.; Ali, Ali J.; Almoula, Jasim M. J. (Scientific Journal of Medical Research, 2022)
Background: Gall bladder (GB) perforation is a common occurrence during laparoscopic cholecystectomy, and knowing the state of the GB before the operation, whether acute, single, or multiple Gall Stones (GS), can assist in directing treatment. Objective: In our study, we clarify the causes that lead to perforation of the gall bladder, so we can avoid them if possible and the risk factors. Setting: Al Jumhoory Teaching Hospital Duration: From May 2020 to August 2021 Patients And Methods: Prospective study for 170 patients underwent laparoscopic cholecystectomy for symptomatic cholelithiasis and calculus cholecystitis. The patients have gall stone disease, either single or multiple GS, and complained of recurrent symptoms of right hypochondrium. Also, patients having acute cholecystitis not responding to medical treatment included. All patients were prepared electively for cholecystectomy and complete investigations and ultrasound of gall bladder and the biliary system performed and anesthesiologic consultation done. We used the standard American method of laparoscopic cholecystectomy. Results: Total number of patients in this study was 170 patients. All patients have undergone laparoscopic cholecystectomy in Al Jumhoory teaching hospital as elective cholecystectomy. Patients with MGS was 93 patient GB perforation occurred in 12 patients, 7 female, and 5 male patients. Patients with SGS were 59 patients, and GB perforation occurred in 11 patients. A total of 8 females and 3 males. The number of acute cholecystitis patients was 18 patients, GB perforation occurred in 8 patients. Conclusion: Gall bladder perforation is not uncommon during the lap. Chole (laparoscopic cholecystectomy) Gall bladder perforation occurs most common during dissection of GB bed by hook cauterization. Traumatic grasper can also cause injury and rupture of GB if used without caution, and excessive traction of GB Perforation occurs in high percentage in acute cholecystitis and with thickening of GB wall. Slipped clips may cause bile leak and or bleeding, which obscure vision, and perforation occurs during dissection. Use of harmonic decreases the risk of gallbladder perforation. In acute cholecystitis and cases with a high rate of perforation, blunt dissection is preferred, and the use of harmonic may reduce the incidence of GB ruptured.